2003
DOI: 10.1007/s00421-003-0796-4
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics during active and passive recovery from a single bout of supramaximal exercise

Abstract: The aim of this work was to study the differences in cardiovascular response during two modes of recovery [active (AR): pedalling at 40 W; and passive (PR): complete rest seated] from a single bout of supramaximal exercise. Eight male amateur soccer players underwent two supramaximal cycle-ergometer tests, each consisting of pedalling against a resistance equivalent to 150% of the maximum workload achieved in a previous incremental test, followed by randomly assigned AR or PR. Cardiodynamic variables were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(107 citation statements)
references
References 37 publications
6
98
0
1
Order By: Relevance
“…Am J Physiol Heart Circ Physiol 292: H2988 -H2996, 2007. First published February 16,2007; doi: 10.1152/ajpheart.00008.2007.-The muscle metaboreflex is enhanced in chronic heart failure (CHF) patients, and this fact has been associated with the early fatigue shown by these patients in response to exercise. In animal studies of CHF, it was found that the limited capacity to enhance ventricular performance is responsible for a functional shift from a cardiac output to a systemic vascular resistance (SVR) increase in the mechanism by which the cardiovascular system raises blood pressure in response to the metaboreflex.…”
mentioning
confidence: 99%
“…Am J Physiol Heart Circ Physiol 292: H2988 -H2996, 2007. First published February 16,2007; doi: 10.1152/ajpheart.00008.2007.-The muscle metaboreflex is enhanced in chronic heart failure (CHF) patients, and this fact has been associated with the early fatigue shown by these patients in response to exercise. In animal studies of CHF, it was found that the limited capacity to enhance ventricular performance is responsible for a functional shift from a cardiac output to a systemic vascular resistance (SVR) increase in the mechanism by which the cardiovascular system raises blood pressure in response to the metaboreflex.…”
mentioning
confidence: 99%
“…With that, the autonomic balance is maintained through the complex interaction between the arterial baroreflex, central and peripheral chemoreflex, ergoreflex and pulmonary stretch reflex 10 . During the exercise, the central hemodynamics and the ventilatory responses are under the control of the autonomic nervous system, which depends on the interaction between the receptors of the brain's motor cortex and the peripheral afferences (baroreceptors, mechano and metaboreceptors) 11 . This system regulates the cardiac output, the vascular conductance and the ventilation, in an attempt to supply the adequate oxygenated blood flow to eliminate muscle metabolic byproducts.…”
Section: Cardiovascular Reflexes Cardiovascular and Ventilatory Contrmentioning
confidence: 99%
“…The baroreceptors work with the control of muscle vasodilation and of heart rate through the sympathetic activation to maintain the blood pressure (BP) and counterbalance any disequilibrium between vascular resistance and cardiac output. On the other hand, the muscle receptors activate the nervous afferences, which, in turn, induce sympathetic-cardiovascular adjustments mediated in response to the mechanical and metabolic conditions of the working muscle 8,11 . There is evidence that the autonomic disequilibrium contributes to the pathogenesis and progression of heart failure.…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there may be a reduction in vascular resistance influenced by an accumulation of metabolites produced in muscle contraction, which, according to MacDonald et al 36 , is one of the factors accounting for vasodilatation and subsequent decrease in peripheral vascular resistance. This may occur so that BP is regulated in a way that permits an adequate circulation for metabolite buffering and supply of the required nutrients 37,38 . This could explain the postexercise decrease in DBP found in the present study, because the protocol with the lowest RI promoted longer PEH.…”
Section: Hr (Bpm)mentioning
confidence: 99%